(untitled) (International Journal of Innovative Computing, 2026)
With the rapid advancement of technology, virtual conferencing, as a new communication medium, are changing people’s traditional communication methods and work models. Through the Internet and advanced communication technology, virtual conferencing eliminates geographical distance and enable people to conduct various communication methods such as video conferencing, audio calls, and real-time chat, making communication easy regardless of time and space. Since COVID-19, there has been a wealth of research on virtual conferencing, especially augmented reality (AR) and virtual reality (VR) conferencing. They are either based on discussions of virtual conferencing technology, reflections on completed virtual conferencing events, or surveys on the user experience of virtual conferencing, but a comprehensive summary of the shared features of virtual conferencing is currently lacking. In this study, we will summarize the key features of virtual conferencing and propose existing issues and challenges in virtual conferencing based on these features, in order to provide directions for improving the quality of virtual conferencing.